Przenikanie się norm prawnych i reguł etycznych w przekroju teoretyczno-prawnym - Maj, Karolina (Kwartalnik Prawa Publicznego, 2017)
Nowadays, the amount of choices is rather frightening, therefore we are still seeking for permanent norms of our behavior. Finding tough moral criteria is problematic, individual morality becomes more complex especially when it transforms into the social morality. Then, the juridical norms, which clearly indicate the borders what is right as well as moral, help. For that reason, we can see the interactions between the juridical norms and the ethical rules which affect on each other with varying degrees and to varying extents. Some of the levels and the fields of norms’ correlation appear to exist only in immaterial sphere, it is impossible to examine them perceptively, however, their existence is undeniable. The main goal of this article is to present the issue of the pervasion of the juridical norms and the ethical rules by defining the term, role and extent of this phenomenon.